Synaptic Ribbon Active Zones in Cone Photoreceptors Operate Independently from One Another - Grassmeyer, Justin J.; Thoreson, Wallace B. (Frontiers in Cellular Neuroscience, 2017)
Cone photoreceptors depolarize in darkness to release glutamate-laden synaptic vesicles. Essential to release is the synaptic ribbon, a structure that helps organize active zones by clustering vesicles near proteins that mediate exocytosis, including voltage-gated Ca2+ channels. Cone terminals have many ribbon-style active zones at which second-order neurons receive input. We asked whether there are functionally significant differences in local Ca2+ influx among ribbons in individual cones. We combined confocal Ca2+ imaging to measure Ca2+ influx at individual ribbons and patch clamp recordings to record whole-cell ICa in salamander cones. We found that the voltage for half-maximal activation (V50) of whole cell ICa in cones averaged -38.1 mV ± 3.05 mV (standard deviation [S.D.]), close to the cone membrane potential in darkness of ca. -40 mV. Ca2+ signals at individual ribbons varied in amplitude from one another and showed greater variability in V50 values than whole-cell ICa, suggesting that Ca2+ signals can differ significantly among ribbons within cones. After accounting for potential sources of technical variability in measurements of Ca2+ signals and for contributions from cone-to-cone differences in ICa, we found that the variability in V50 values for ribbon Ca2+ signals within individual cones showed a S.D. of 2.5 mV. Simulating local differences in Ca2+ channel activity at two ribbons by shifting the V50 value of ICa by ±2.5 mV (1 S.D.) about the mean suggests that when the membrane depolarizes to -40 mV, two ribbons could experience differences in Ca2+ influx of >45%. Further evidence that local Ca2+ changes at ribbons can be regulated independently was obtained in experiments showing that activation of inhibitory feedback from horizontal cells to cones in paired recordings changed both amplitude and V50 of Ca2+ signals at individual ribbons. By varying the strength of synaptic output, differences in voltage dependence and amplitude of Ca2+ signals at individual ribbons shape the information transmitted from cones to downstream neurons in vision.